2007
DOI: 10.1097/mph.0b013e3180645170
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Ghrelin Levels in Various Stages of Development of Iron Deficiency Anemia

Abstract: A significant positive correlation was demonstrated between iron status of the body and levels of ghrelin. Decrease in ghrelin levels in IDA can lead to loss of appetite, desire to eat diverse foods with resultant delay in growth and development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 20 publications
3
24
1
2
Order By: Relevance
“…After iron supplementation, ghrelin concentration tended to be increased compared with their basal ghrelin concentrations. These results agree with the findings of İsguven et al [6] and with Akarsu et al, [7] who previously noted that total ghrelin was decreased in children with IDA. Like them, we also assumed that loss of appetite correlated with a decreased level of ghrelin in adult females with IDA.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…After iron supplementation, ghrelin concentration tended to be increased compared with their basal ghrelin concentrations. These results agree with the findings of İsguven et al [6] and with Akarsu et al, [7] who previously noted that total ghrelin was decreased in children with IDA. Like them, we also assumed that loss of appetite correlated with a decreased level of ghrelin in adult females with IDA.…”
Section: Discussionsupporting
confidence: 83%
“…But if iron levels are too low, the number of red blood cells and hemoglobin production falls below normal, resulting in IDA [1]. This anemia is also associated with some bioactive peptide hormonal changes [4,7]. In this study, both saliva and serum basal hormone acylated ghrelin concentrations in subjects with IDA were significantly lower levels when compared with the control group without IDA.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…After identification of ghrelin in mammals by Kojima et al [2] so many relative studies were conducted on ghrelin properties. Studies conducted during last decade suggested various specifies and functions for ghrelin, such as GH-releasing [3] , osteogenesis [4,5] , hematopoiesis [6,7] , food intake and energy balance and regulation [8,9] , endocrine/ paracrine roles in pancreas [10,11] , and currently antioxidative effects [12,13] . Peptide structure of chicken ghrelin has 26 amino acids with 54% similarity to rat ghrelin [14] .…”
Section: Introductionmentioning
confidence: 99%